PEDAGOGICAL CONDITIONS FOR THE FORMATION OF SPORTS MOTIVATION - Talipdzhanov Alijan Akramovich; Akhmedova Nargiza Alidzhanovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
based on the theoretical analysis of scientific and methodological literature, the essence and content of sports motivation and the features of its connection with the personal qualities of athletes are determined. The pedagogical conditions for the formation of sports motivation of volleyball players aged 15-16 are revealed.